2001
DOI: 10.4141/p00-091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source, timing and placement of nitrogen on grain yield and nitrogen removal of durum wheat under reduced- and conventional-tillage management

Abstract: . 2001. Influence of source, timing and placement of nitrogen on grain yield and nitrogen removal of durum wheat under reduced-and conventional-tillage management. Can. J. Plant Sci. 81: 17-27. Effective fertilizer management is critical to maintain economic production and protect long-term environmental quality. Field studies were conducted over 4 yr at two locations in southwestern Manitoba to determine the effect of source, timing and placement of N on grain yield and N recovery of durum wheat (Triticum dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
6
23
1
Order By: Relevance
“…However, SB is more effective than Br in enhancing seed yield and N uptake in seed. These observations are consistent with earlier findings that banding N is superior to broadcasting (Malhi and Nyborg 1992;Grant et al 2001). However, under very dry conditions seedling establishment may be reduced on SB compared to Br.…”
Section: Broadcast Versus Side-banding Ureasupporting
confidence: 93%
See 1 more Smart Citation
“…However, SB is more effective than Br in enhancing seed yield and N uptake in seed. These observations are consistent with earlier findings that banding N is superior to broadcasting (Malhi and Nyborg 1992;Grant et al 2001). However, under very dry conditions seedling establishment may be reduced on SB compared to Br.…”
Section: Broadcast Versus Side-banding Ureasupporting
confidence: 93%
“…Hence, it is not surprising that few differences were observed between SB-P and SP-P when P was applied at 7 to 10 kg P ha (1 . At higher rates of P, SB-P is safer than SP-P (Grant et al 2001;Lafond et al 2003;Anonymous 2006c).…”
Section: Plant Density ----------------------------------------------mentioning
confidence: 99%
“…For example, compared with Br_U, SB_U had higher seed yield, seed protein content, seed N uptake and straw N uptake at 1 site-year. Earlier research has also shown that banding was superior to broadcasting N on NT systems Grant et al 2001), suggesting that our results were generally consistent with previous work.…”
Section: N Fertilizer Placement Methodssupporting
confidence: 82%
“…There was no overall significant influence of fertilizer form on other crop parameters, results which generally agree with the findings of earlier research that concluded that all N forms are effective in improving crop yield and/or N recovery when applied properly to increase accessibility and prevent any gaseous N loss (Touchton and Hargrove 1982;Malhi et al 1996;Grant et al 2001;Lafond et al 2003). There was a significant S )F interaction indicating variable results at the individual site-year level, but no clear trends were discernable.…”
Section: N Fertilizer Form/formulationsupporting
confidence: 81%
“…These results were also further supported by Mengel et al (1982) who observed an increase in grain yield when N fertilizer was injected below the soil surface compared to surface applied N sources. Grant et al (2001) also observed that banding fertilizer increased grain yield. In wheat, Blackshaw et al (2004) observed a 12% increase when banding ammonium nitrate compared to broadcast ammonium nitrate during spring application.…”
Section: Discussionmentioning
confidence: 68%